2022
DOI: 10.1111/jmwh.13366
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant use During Pregnancy: Knowledge, Attitudes, and Decision‐Making of Patients and Providers

Abstract: Introduction: Despite the risks associated with untreated perinatal depression and anxiety, both patients and clinicians are less likely to follow evidence-based guidelines including the use of antidepressants during pregnancy. The aim of this integrative review was to describe the perspectives of both patients and prescribing health care providers regarding the use of antidepressants during pregnancy. Methods:We performed a literature search in PubMed, CINAHL, ProQuest Central, and PsychINFO. Inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Ultimately, such variations in practices based on provider beliefs, comfort levels, and a lack of guidance of high-quality recommendations leave many women untreated for depression. 35 All mothers in our sample reported using cannabis to address mental health concerns, yet less than a quarter screened positive for anxiety or depression, and 88% were classified as having mild or no psychological distress in the composite PHQ-4. Although substantial differentially missing data for PHQ-4 limits our ability to draw conclusions about psychological distress between those who did and did not use psychiatric medications, the rate of self-reported symptoms (100% of the sample) is higher than it appeared on the PHQ-4.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Ultimately, such variations in practices based on provider beliefs, comfort levels, and a lack of guidance of high-quality recommendations leave many women untreated for depression. 35 All mothers in our sample reported using cannabis to address mental health concerns, yet less than a quarter screened positive for anxiety or depression, and 88% were classified as having mild or no psychological distress in the composite PHQ-4. Although substantial differentially missing data for PHQ-4 limits our ability to draw conclusions about psychological distress between those who did and did not use psychiatric medications, the rate of self-reported symptoms (100% of the sample) is higher than it appeared on the PHQ-4.…”
Section: Discussionmentioning
confidence: 87%
“…34 This lack of concrete direction may contribute to physician uncertainty about recommending pharmacologic options when offering interventions for mental illnesses perinatally. 35 A 2012 study of postpartum depression found that women were more likely to be prescribed medication treatment (with or without counseling) if their medical practice received specialized training. 36 A 2022 review on the knowledge, attitudes, and decision-making process of patients and providers regarding antidepressant use during pregnancy found that while physicians were confident in these skills, many overestimated the teratogenic risk, and between 20% and 74% avoided starting an antidepressant during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…20 21 In women with a perinatal mental illness, elevated risk perception of adverse outcomes in offspring due to psychotropic medication exposure often affects the decision-making regarding their treatment. [22][23][24] The ongoing debate concerning the reproductive safety of these medications may contribute to confusion and decisional conflicts regarding pharmacological treatment, both among women and healthcare providers. 25 26 Several studies have shown that the perceived teratogenic risk of psychotropic medication use may be unrealistically elevated among pregnant women or recent mothers.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Negative emotions, including guilt and shame have been reported in people who have history of exposures during pregnancy (Cleveland & Bonugli, 2014; Irwin et al, 2005). Studies have shown that feelings of guilt and worry persist regardless of the decision the individual made to stop or continue medication use during pregnancy even when they received reassuring information from their healthcare provider (Eakley & Lyndon, 2022; Mulder et al, 2012). In addition, increasing evidence suggests that anxiety occurs frequently during pregnancy and pregnancy‐related anxiety, characterized by pregnancy specific fears and worries, may be a specific type of anxiety in pregnant populations (Heron et al, 2004; Huizink et al, 2004).…”
Section: Introductionmentioning
confidence: 99%